2013
DOI: 10.1179/2047773213y.0000000107
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of enteroparasitosis in urban slums of Belo Horizonte-Brazil. Presence of enteroparasites as a risk factor in the family group

Abstract: The present study evaluates the prevalence of enteroparasitosis in the urban slums of Belo Horizonte, Brazil and the risk of transmitting enteroparasites to the family members of infected individuals. Stool samples were collected and examined at clinical laboratories near each slum. Individuals were identified and classified as positive for parasitosis (IP z ), and individuals with negative stool tests were classified as negative for parasitosis (IP 2 ) and enrolled as control patients. We collected samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
3
16
1
5
Order By: Relevance
“…G. lamblia was the most prevalent parasite in the examined population (50.8%), a finding that corroborates those of other coproparasitological studies conducted in Brazil (1,(5)(6)(7)13,16) . The transmission of G. lamblia occurs primarily by contaminated water and unclean hands.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…G. lamblia was the most prevalent parasite in the examined population (50.8%), a finding that corroborates those of other coproparasitological studies conducted in Brazil (1,(5)(6)(7)13,16) . The transmission of G. lamblia occurs primarily by contaminated water and unclean hands.…”
Section: Discussionsupporting
confidence: 90%
“…A study in municipal day care centers in Niterói, Rio de Janeiro (6) found that the prevalence of parasites was 61.3%, with a predominance of Giardia lamblia (G.lamblia). In Minas Gerais (MG), a study found that the prevalence of intestinal parasites was 34.6% (n=1338) in urban slums (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal parasitoses are neglected conditions linked to poverty and poor sanitation, being more prevalent in developing countries [1,2]. Among the protozoan parasites, Giardia intestinalis is present in distinct sociodemographic settings, being a potentially zoonotic pathogen [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different ameba species, E. histolytica is the only species considered invasive, especially in tropical regions and communities living in inadequate sanitary conditions [19]. Although many individuals are contaminated by commensal amoebae, most infections are asymptomatic [20,21]. The results show low numbers of this parasite, which indicates that the parasite may not be endemic in the region.…”
Section: Discussionmentioning
confidence: 99%